Urban improvement, a mechanism of tourism development: Tébessa (Algeria) as a model (Journal of Planner and Development, 2020)
The tourism industry has become, currently, an art, an industry and a science. It is also one of the components that make up touristic regions. Tourist attractions are no longer the exclusive visits of museums and archeological sites, but also involve other service facilities. It is, therefore, imperative that the authorities should become aware of the degradation of tourist resorts and prevent them from getting worse. Moreover, the authorities should take a set of decisions concerning the protection of the urban aspect with its historical, social, and environmental dimensions, as well as, adapting it to the modern requirements that can bring comfort to the citizens and tourists at physical and psychological levels.